Additional Freshwater Fishes of Simeulue Island, with Special Reference to the Presence of Sharp-Nosed River Mullet Cestraeus oxyrhyncus (Actinopterygii: Mugilidae) - Iqbal, Muhammad; Amey, Tom; Kusuma, Irda; Alim, Satri Sara; Amin, Afri (BIO PALEMBANICA, 2025)
This study reports new records of freshwater fish species from Simeulue Island, Aceh Province, Indonesia. A biodiversity survey conducted in July 2021 revealed five additional fish species not previously documented on the island, including Acentrogobius sp., Giuris margaritaceus, Cestraeus oxyrhyncus, Poecilia reticulata and Clarias sp. The survey also confirmed the presence of introduced species, such as Nile Tilapia Oreochromis niloticus and Guppy Poecilia reticulata, highlighting the need for monitoring and managing non-native species in the region. The discovery of C. oxyrhyncus, currently classified as Data Deficient, accentuates the importance of further research to determine its threats, ecology, population size, and trends. This study contributes to the understanding of freshwater fish diversity on Simeulue Island and emphasises the importance of conservation efforts to protect the biodiversity of small islands in Indonesia. Keywords: Aceh, freshwater fish, Indonesia, Simeulue Island, Sumatra.